El papel de la fraseología en el discurso publicitario: sugerencias para un análisis multidisciplinar - Fernández Toledo, Piedad; Mena Martínez, Flor (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2007)
This paper envisages Phraseology as a key factor to consider in any approach to the language of Advertising, and suggests some guidelines for its analysis. A close link is drawn between Phraseology and Genre, two linguistic areas in which the role of context determines to a great extent the interpretation of linguistic phenomena. We propose an approach based on Genre Theory as the ideal tool for the study of discourse, and more specifically of advertising discourse. This approach departs from pragmatic and socio-cultural considerations and explores the rest of linguistic aspects and functions as related to, if not dependent on, these considerations, in a given Discourse Community. Within this frame of application, we discuss the relationship between phraseology and prototypical advertising genres, identifying extra-textual factors that come up as essential for their identification and embodiment.